Optogenetic mapping of cerebellar inhibitory circuitry reveals spatially biased coordination of interneurons via electrical synapses - Kim, Jinsook (2014)
We used high-speed optogenetic mapping technology to examine the spatial organization of local inhibitory circuits formed by cerebellar interneurons. Transgenic mice expressing channelrhodopsin-2 exclusively in molecular layer interneurons allowed us to focally photostimulate these neurons, while measuring resulting responses in postsynaptic Purkinje cells. This approach revealed that interneurons converge upon Purkinje cells over a broad area and that at least seven interneurons form functional synapses with a single Purkinje cell. The number of converging interneurons was reduced by treatment with gap junction blockers, revealing that electrical synapses between interneurons contribute substantially to the spatial convergence. Remarkably, gap junction blockers affected convergence in sagittal slices, but not in coronal slices, indicating a sagittal bias in electrical coupling between interneurons. We conclude that electrical synapse networks spatially coordinate interneurons in the cerebellum and may also serve this function in other brain regions.